ASIC-E4: Interplay of Beta-Amyloid, Synaptic Density and Neuroinflammation in Cognitively Normal Volunteers With Three Levels of Genetic Risk for Late-Onset Alzheimer's Disease – Study Protocol and Baseline Characteristics - Snellman, Anniina; Ekblad, Laura L.; Koivumäki, Mikko; Lindgrén, Noora; Tuisku, Jouni; Perälä, Merja; Kallio, Lila; Lehtonen, Riina; Saunavaara, Virva; Saunavaara, Jani; Oikonen, Vesa; Aarnio, Richard; et al. (Frontiers in Neurology, 2022)
Background Detailed characterization of early pathophysiological changes in preclinical Alzheimer's disease (AD) is necessary to enable development of correctly targeted and timed disease-modifying treatments. ASIC-E4 study (“Beta-Amyloid, Synaptic loss, Inflammation and Cognition in healthy APOE ε4 carriers”) combines state-of-the-art neuroimaging and fluid-based biomarker measurements to study the early interplay of three key pathological features of AD, i.e., beta-amyloid (Aβ) deposition, neuroinflammation and synaptic dysfunction and loss in cognitively normal volunteers with three different levels of genetic (APOE-related) risk for late-onset AD. Objective Here, our objective is to describe the study design, used protocols and baseline demographics of the ASIC-E4 study. Methods/Design ASIC-E4 is a prospective observational multimodal imaging study performed in Turku PET Centre in collaboration with University of Gothenburg. Cognitively normal 60–75-year-old-individuals with known APOE ε4/ε4 genotype were recruited via local Auria Biobank (Turku, Finland). Recruitment of the project has been completed in July 2020 and 63 individuals were enrolled to three study groups (Group 1: APOE ε4/ε4, N = 19; Group 2: APOE ε4/ε3, N = 22; Group 3: APOE ε3/ε3, N = 22). At baseline, all participants will undergo positron emission tomography imaging with tracers targeted against Aβ deposition (11C-PIB), activated glia (11C-PK11195) and synaptic vesicle glycoprotein 2A (11C-UCB-J), two brain magnetic resonance imaging scans, and extensive cognitive testing. In addition, blood samples are collected for various laboratory measurements and blood biomarker analysis and cerebrospinal fluid samples are collected from a subset of participants based on additional voluntary informed consent. To evaluate the predictive value of the early neuroimaging findings, neuropsychological evaluation and blood biomarker measurements will be repeated after a 4-year follow-up period. Discussion Results of the ASIC-E4 project will bridge the gap related to limited knowledge of the synaptic and inflammatory changes and their association with each other and Aβ in “at-risk” individuals. Thorough in vivo characterization of the biomarker profiles in this population will produce valuable information for diagnostic purposes and future drug development, where the field has already started to look beyond Aβ.